2007
DOI: 10.1080/03031853.2007.9523774
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Price Volatility of Certain Field Crops in South Africa using the ARCH/GARCH Approach

Abstract: The conditional volatility in the daily spot prices of the crops traded on the South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 7 publications
1
38
0
2
Order By: Relevance
“…The Augmented Dickey Fuller (ADF) test is used for testing the stationarity of the price series of wheat and rice. Jordaan et al (2007), Karali & Power (2013), May (2010), Moledina et al (2004), Swaray (2007) and Yang et al (2001) estimated price volatility employing generalised auto regressive heteroscedasticity (GARCH/ARCH) technique. It is argued that by distinguishing predictable and unpredictable components of prices, these techniques provide accurate estimates of volatility.…”
Section: Price Volatilitymentioning
confidence: 99%
“…The Augmented Dickey Fuller (ADF) test is used for testing the stationarity of the price series of wheat and rice. Jordaan et al (2007), Karali & Power (2013), May (2010), Moledina et al (2004), Swaray (2007) and Yang et al (2001) estimated price volatility employing generalised auto regressive heteroscedasticity (GARCH/ARCH) technique. It is argued that by distinguishing predictable and unpredictable components of prices, these techniques provide accurate estimates of volatility.…”
Section: Price Volatilitymentioning
confidence: 99%
“…Groenewald et al (2003) argue that the variability of input and product prices have increased since the deregulation of the agricultural commodities market in the mid 1990s. Jordaan et al (2007) compared price volatility of field crops that are traded on SAFEX (yellow maize, white maize, wheat, sunflower seed and soybeans). They found the volatility associated with the price of white and yellow maize to be substantially higher than that of other crops that are traded on SAFEX.…”
Section: Introductionmentioning
confidence: 99%
“…The estimates of equation (2) and (3) were used to test the persistence of volatility in the selected food crop in the study period. The GARCH approach has been used to study volatility in variables by many researchers (Moledina et al, 2003;Ghebrechristos, 2004& Jordaan et al, 2007. The model relied on the assumption of homoscedasticity -instead of considering heteroscedasticity as a problem to be solved.…”
Section: Measuring Food Crop Output Volatilitymentioning
confidence: 99%
“…Also, the mean food crop outputs showed a progressive growth rate across the policy programme periods since 1961, and were best during Post Structural Adjustment period (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009). Jordaan et al, (2007) in South Africa, used standard error of the ARIMA process as the measure of volatility of prices of wheat and soybeans and found that volatility in the two crops was constant over time.…”
Section: Introductionmentioning
confidence: 99%